Lack of 'common sense' in the climate change debate: Media behaviour and climate change awareness in the UK. (January 2023) - Ruiu, Maria Laura; Ruiu, Gabriele; Ragnedda, Massimo
Based on an online survey conducted among a representative sample in the United Kingdom ( n  = 1013), this article investigates the role of traditional and new media in predicting climate change awareness. It suggests that individuals make choices under an ideological convincement that is organised within specific cultural and political-economic boundaries. It shows that the Gramscian concept of cultural hegemony is still valuable to make sense of an incessant process of formation and fragmentation of equilibria between social groups. Interpreting hegemony as a not totalitarian communicative process also suggests that the media represent a ground for counterhegemonies to flourish and trigger political transformation. This study constructs two indexes of both scepticism and advocacy of climate change by showing some traits of these two perspectives in the United Kingdom. It also shows that the division between sceptics and advocates' convincement is not 'black and white', but a transitional space exists between hegemonic and counter-hegemonic forces.